High-skilled labour mobility in an era of protectionism: Foreign startups and India - Arpita Mikherjee; Avantika Kapoor; Angana Parashar (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Realisation that foreign startups have the potential to add new and innovative products and services to the market, bring in investment and create more jobs compared to traditional firms, a number of countries are providing fiscal and non-fiscal incentives, including startup visas, to attract them. In spite of being a proponent of liberalisation of high-skilled labour mobility in its international engagements, India is yet to take a position on incentives to foreign startups and/or entrepreneurs and startups visas. Given this background, this paper examines the policies of other countries with respect to incentives given to the foreign startups, including startups visas, and how India can learn from global best practices. It analyses India's advantages and comparative position vis-à-vis select developed and developing countries as a startup hub. It examines the contribution of foreign startups in India and the barriers that they face. It then makes policy recommendations on how to attract foreign startups to bring in investment, technology, create high quality jobs, mitigate and enhance their participation in India's growth and development towards an innovation economy. It also makes policy recommendations on how India can synergise its domestic policies with international negotiations to leverage its position in global platforms such as the G20 and the WTO.
Keywords: C83; F20; F13; F66; L26; 330; High-skilled Mobility; Protectionism; Startups; India; Survey; Policy